ANALISIS DAMPAK DESENTRALISASI FISKAL TERHADAP OUTCOMES PELAYANAN PUBLIK BIDANG PENDIDIKAN (Studi kasus: Provinsi DKI Jakarta) - Noval Akhmad Huda; Hadi Sasana (Universitas Diponegoro, 2013)
Fiscal decentralization was held since 2001 is purpose to give more capacity of public service that government do for people. This research is purpose to see the effect of fiscal decentralization to outcomes of public service in education sector. This research path analysis that use output variable as intervening and want to see the direct and in direct effect of fiscal decentralization to outcomes of education sector. And finally it can take the better policy to repair the result of public service from the output until the outcome.This research use panel data from six city and residence in Jakarta in 2006 until 2010. The method to get the result of this research is use path analysis approach to find the direct and in direct effect of fiscal decentralization to output and outcome of education sector of public service.The result of this research shows that fiscal decentralization have better effect for outcome of education sector of public service in that direct effect. Fiscal decentralization has positive effect to graduation rate in high school and vocational school. If fiscal decentralization increase one percent graduation rate rise up to 0.008 percent, but graduation rate have no significant effect for outcomes of education. Fiscal decentralization has positive effect in level of drop out of high school and vocational school, if fiscal decentralization increase one percent drop out level will be increase 0.547 percent, so fiscal decentralization not give better effect in drop out level yet as expected.